2000
DOI: 10.1097/00005131-200003000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Study of Intramedullary Nails Inserted With and Without Reaming for the Treatment of Open and Closed Fractures of the Tibial Shaft

Abstract: Our findings support the use of reamed insertion of IM nails for the treatment of closed tibia fractures, which led to earlier time to union without increased complications. In addition, canal reaming did not increase the risk of complications in open tibia fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
155
0
15

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(178 citation statements)
references
References 44 publications
8
155
0
15
Order By: Relevance
“…Three of these studies were found in both the PubMed and EMBASE databases [11,31,37]. Twenty-two studies [21,23,24,[31][32][33][34][35]38 [15, 17-19, 22, 25-30, 36, 40, 42, 48] were excluded because they included adults, and we were unable to separate the adult data from those of patients \18 years of age. Three papers [29,37,43] were excluded because they were review papers and not studies that included patient treatment and follow-up information.…”
Section: Methodsmentioning
confidence: 99%
“…Three of these studies were found in both the PubMed and EMBASE databases [11,31,37]. Twenty-two studies [21,23,24,[31][32][33][34][35]38 [15, 17-19, 22, 25-30, 36, 40, 42, 48] were excluded because they included adults, and we were unable to separate the adult data from those of patients \18 years of age. Three papers [29,37,43] were excluded because they were review papers and not studies that included patient treatment and follow-up information.…”
Section: Methodsmentioning
confidence: 99%
“…Another six articles were excluded (Appendix 1. Supplemental materials are available with the online version of CORR 1 ), leaving 14 eligible studies [2,12,13,19,22,25,27,30,39,[41][42][43][44][45] for our survey. The weighted kappa for full-text article eligibility was good (j = 0.79; 95% CI, 0.46-0.98).…”
Section: Literature Searchmentioning
confidence: 99%
“…Eight of the studies were randomized [2,13,25,27,30,41,42,45] and six were quasirandomized controlled trials [12,19,22,39,43,44]. Five studies included patients with open and closed fractures [13,27,41,42,45]; however, we extracted and included data only from the subset of patients with open fractures in these trials. In Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations